2010
DOI: 10.1007/s11901-010-0031-9
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis C Assays: The Pitfalls of Polymerase Chain Reaction and Genotyping

Abstract: Hepatitis C virus (HCV) continues to represent a worldwide threat to the lives of millions of people chronically infected with the virus. Accurately identifying the virus in terms of genetic characteristics, as well as quantifying its replicative equilibrium both during steady state and in the presence of antiviral therapy, is critically important for providing optimal care and prognoses. Genotype testing continues to evolve; however, it is important to recognize its limitations, particularly as we enter the w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…One recognized deficiency of most genotyping assays is their limited sensitivity for detecting mixed‐genotype infections, and the reported prevalence is variable depending on the genotyping methodology used . Most of the available assays share the requirement of an initial target amplification step to generate appropriate amounts of template for genotypic analysis.…”
Section: Discussionmentioning
confidence: 99%
“…One recognized deficiency of most genotyping assays is their limited sensitivity for detecting mixed‐genotype infections, and the reported prevalence is variable depending on the genotyping methodology used . Most of the available assays share the requirement of an initial target amplification step to generate appropriate amounts of template for genotypic analysis.…”
Section: Discussionmentioning
confidence: 99%
“…As a result, genotypes present at lower proportional levels in a mix or with lower affinity could be missed or mistyped (Hnatyszyn, 2005). Both direct sequencing and restriction fragment length polymorphism assays seem to require 10% to 30% prevalence of minor strains before they can detect them (Qian et al, 2000;Frederick, 2010). Hybridization based genotyping methods represent an attractive genotyping option compared to sequencing methods.…”
Section: Methods For Hcv Genotyping and Limitations With Mixed Infectmentioning
confidence: 99%
“…The potential advantage of hybridization assays is their ability to detect mixed populations of virus with a prevalence as low as 2% (Qian et al, 2000). However similar to most genotyping methods, it involves PCR amplification of target regions of the viral genome and is confined by the advantages and disadvantages associated with PCR (Hnatyszyn, 2006;Frederick, 2010). It was reported that the latest version of the LiPA (Versant LiPA v2.0, Bayer HealthCare-Diagnostics), which targets both the 5′ UTR and the core protein, seems to have improved on the problem of subtyping and has performed better than a direct sequencing assay (Trugene) as well as an earlier version of the hybridization assay (Versant LiPA v1.0).…”
Section: Methods For Hcv Genotyping and Limitations With Mixed Infectmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, many samples can be analysed simultaneously. In addition, real-time PCR makes quantitative assay of RNA much more precise and reproducible because it relies on threshold cycle values determined during the exponential phase of PCR rather than endpoint [14,15].…”
Section: Introductionmentioning
confidence: 99%